Pathogenesis and regenerative therapy in vitiligo and alopecia areata: focus on hair follicle - Zhou, Yuan; Zhang, Yu-Xuan; Xiong, Yu-Yun; Li, Yu-Mei (Frontiers in Medicine, 2025)
Vitiligo is an autoimmune disease characterized by the loss of functional melanocytes in the hair follicles and epidermis, leading to white patches on the skin and mucous membranes. Alopecia areata (AA) is a common immune-mediated condition in which autoimmune attack on hair follicles cause non-scarring hair loss. Both diseases significantly impact patients’s physical and mental health. Hair follicles, dynamic mini-organs, house diverse stem cell populations that form hair structures. Melanocyte stem cell (McSCs) and hair follicle stem cells (HFSC) located in the hair follicle bulge contribute to follicular structures during each anagen phase of the hair cycle, synchronizing periodic activities to impact color to the hair. Hair follicle dysfunction may contribute to hair loss and could potentially interfere with repigmentation efforts in vitiligo lesions. This article reviews the role of hair follicles in the pathogenesis, clinical manifestations, and therapeutic options for vitiligo and AA, aiming to deepen clinicians’ understanding of follicular involvement in these diseases and explore potential treatment avenues.